The Relationship Between High Emotional Intelligence and Stress in Medical Students of Medicine Pelita Harapan University During the Covid-19 Pandemic - Suryadinata, Neneng; Amadea, Sabrina; Conney, Fred Rich (Medicinus, 2022)
Background: The World Health Organization (WHO) has declared Coronavirus Disease 2019 (COVID-19) a global pandemic. This also has an impact on students' lives. Most of the students have been in a stressful condition due to changes in the online teaching and learning process as an adaptation to COVID-19. Although it has been reported that emotional intelligence can reduce stress, there are still a few studies that study about the relationship between the two during the COVID-19 pandemic, especially among medical students.Methods: A cross-sectional using comparative numerical analysis was conducted with 305 medical students. Data were collected by an online survey using Emotional Intelligence Appraisal (EIA) questionnaire, and Medical Student Stressor Questionnaire (MSSQ). Statistical analysis was done using Statistical Package for the Social Sciences (SPSS) version 25.Results: The EIA questionnaire showed that there were 1.3% low EI groups, 38.7% normal EI groups, and 60.0% high EI groups. The MSSQ questionnaire showed that there was 24% mild stress, 49% moderate stress, 26% severe stress, and 1% very severe stress. Normal data distribution was obtained through the Kolmogorov-Smirnov test, so that the T-test could be used with a 95% confidence degree (p-value <0.05). T-test analysis in the high EI group with an average stress (1.76±0.64) and the normal EI group with an average stress (1.40±0.75) showed a significant difference with p-value = 0.008.Conclusion: In accordance with the hypothesis in this study, during the COVID-19 pandemic, there is a significant relationship between high emotional intelligence and stress in UPH Medical Faculty students.